Hatchery tanks induce intense reduction in microbiota diversity associated with gills and guts of two endemic species of the São Francisco River - Damasceno, Maria Rosilene Alves; Lemes, Camila Gracyelle de Carvalho; Braga, Lucélia Sandra Silva Barbosa; Tizioto, Polyana Cristine; Montenegro, Horácio; Paduan, Marcela; Pereira, Josielda Gomes; Cordeiro, Isabella Ferreira; Rocha, Lorrana Cachuite Mendes; da Silva, Sibele Aryadne; Sanchez, Angélica Bianchini; Lima, Wanderson Geraldo; et al. (Frontiers in Microbiology, 2022)
The São Francisco River (SFR), one of the main Brazilian rivers, has suffered cumulative anthropogenic impacts, leading to ever-decreasing fish stocks and environmental, economic, and social consequences. Rhinelepis aspera and Prochilodus argenteus are medium-sized, bottom-feeding, and rheophilic fishes from the SFR that suffer from these actions. Both species are targeted for spawning and restocking operations due to their relevance in artisanal fisheries, commercial activities, and conservation concerns. Using high-throughput sequencing of the 16S rRNA gene, we characterized the microbiome present in the gills and guts of these species recruited from an impacted SFR region and hatchery tanks (HT). Our results showed that bacterial diversity from the gill and gut at the genera level in both fish species from HT is 87% smaller than in species from the SFR. Furthermore, only 15% and 29% of bacterial genera are shared between gills and guts in R. aspera and P. argenteus from SFR, respectively, showing an intimate relationship between functional differences in organs. In both species from SFR, pathogenic, xenobiont-degrading, and cyanotoxin-producer bacterial genera were found, indicating the critical pollution scenario in which the river finds itself. This study allowed us to conclude that the conditions imposed on fish in the HT act as important modulators of microbial diversity in the analyzed tissues. It also raises questions regarding the effects of these conditions on hatchery spawn fish and their suitability for restocking activities, aggravated by the narrow genetic diversity associated with such freshwater systems.